The Impact Of Coaching Behaviours On The Sustainable Development Of Youth Athletes - Shuai, Zhang; Keat, Ooi Boon; Tham, Jacquline (Migration Letters, 2024)
The development of youth athletes is the foundation of sports advancement. It is imperative to assist youth athletes in maintaining a positive mindset and motivation throughout their athletic career, overcoming challenges and setbacks, striking a balance between sports development and other domains, and achieving comprehensive personal growth. The coach’s conduct plays a crucial role in the developmental journey of youth athletes, as they serve as the primary mentor and influencer. Therefore, this study adopts the self-determination theory as a theoretical framework and investigates the association between coaching behaviours and the sustainable development of youth athletes. It aims to explore which coaching behaviours can facilitate the cultivation of self-determination ability among youth athletes through questionnaire surveys, thereby fostering their long-term athletic career progression. The data for this study were collected from a research questionnaire administered to 321 youth athletes. Structural Equation Modeling (SEM) of AMOS was employed for data analysis. The study’s findings suggest that coaching behaviours significantly impact youth athletes’ self-determination ability and sustainable development. Moreover, it was found that the self-determination ability of youth athletes plays a mediating role in this relationship. These results offer valuable insights for regulating coaching behaviours.